Social Competence in Children With Autism - Yavuz, H. Melis; Selçuk, Bilge; Korkmaz, Barış (Taylor & Francis, 2017)
Objectives: This paper investigates the associations of social competence with cognitive representation and communication skills in children with Autism Spectrum Disorders (ASD), by measuring these skills in an expansive way through assessing both mental and internal-state understanding, and verbal and non-verbal communication. Methods: The data were collected from 45 Turkish children (Mage=8.52 years, SD=3.05, min-max=3–14) with a diagnosis of ASD. Individual assessments were used to measure mental- and internal-state understanding. Teacher-rated scales were used to assess child’s verbal and non-verbal communication skills, and social competence. Results: The results showed that social competence, cognitive representation, verbal and non-verbal communication skills were all significantly associated, but over and above cognitive representation skills and verbal communication, non-verbal communication had a salient role in adaptive social relationships of children with ASD. Conclusions: These findings have important applied implications for intervention studies and suggest that improvements of non-verbal communication skills in children with ASD might be important for increasing their positive social relations.
Keywords: Social competence; Cognitive representation; Autism spectrum disorders; Turkish children; Non-verbal communication; Verbal communication; Autism; Communication skills